Finansowanie polityki ekologicznej - Burzyńska, Dorota (Financing Ecological Policy, 2009)
Ecological security of a national economy is the basic purpose of ecological policy. Separation of this policy is very important from the point of view of economic policy because managing the processes of natural environment protection on many fields enables high efficiency of such activities. The rules of creating and implementing ecological policy depend on the state of natural environment, the development and condition of national economy, and also a general state policy and international commitments regarding natural environment. The key role plays the development of ecological investments, which is depended first of all on instruments of the state ecological policy. During the last few years we can observe that enterprises' own founds and EU founds are the basic groups of financial resources in ecology.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 21-28